Treatise of Human Nature: Being an Attempt to introduce the experimental Method of Reasoning into Moral Subjects - Hume, David (Epub, 2009)
A Treatise of Human Nature , first published between 1739 and 1740, is a philosophical text by the Scottish philosopher David Hume. The work contains three books: "Of the Understanding", "Of the Passions" and "Of Morals". Written by Hume when he was 26, it is considered by many to be Hume's best work and one of the most important books in philosophy's history.